2009
DOI: 10.1086/599248
|View full text |Cite
|
Sign up to set email alerts
|

Does Race Matter in Neighborhood Preferences? Results from a Video Experiment

Abstract: Persistent racial residential segregation is often seen as the result of the preferences of whites and blacks: whites prefer to live with whites while blacks wish to live near many other blacks. The origin of these preferences and their social psychological underpinnings are hotly debated. Are neighborhood preferences colorblind or race-conscious? Does neighborhood racial composition have a net influence upon preferences or is race a proxy for social class? If preferences are race-conscious, is this more a mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
202
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(217 citation statements)
references
References 40 publications
9
202
0
2
Order By: Relevance
“…Along these lines, Krysan and Farley (2002) found that blacks were uncomfortable moving into all white neighborhoods because they perceived such neighborhoods as more hostile and feared greater discrimination. In a later experimental study, Krysan, Couper, Farley, and Forman (2009) showed that independent of social class, blacks found diverse neighborhoods to be the most desirable, followed by all black, and all white neighborhoods.…”
Section: Racial Heterogeneity and Mental Healthmentioning
confidence: 95%
See 1 more Smart Citation
“…Along these lines, Krysan and Farley (2002) found that blacks were uncomfortable moving into all white neighborhoods because they perceived such neighborhoods as more hostile and feared greater discrimination. In a later experimental study, Krysan, Couper, Farley, and Forman (2009) showed that independent of social class, blacks found diverse neighborhoods to be the most desirable, followed by all black, and all white neighborhoods.…”
Section: Racial Heterogeneity and Mental Healthmentioning
confidence: 95%
“…However, whites' views of diverse neighborhoods also became increasingly negative as their negative stereotypes of blacks and the neighborhoods they reside in increased (Krysan et al, 2009). Whereas perceived discrimination and in-group identity did not significantly influence the neighborhood preferences of blacks, negative racial stereotyping and in-group identity (particularly positive feelings towards one's own group) significantly influenced preferences for whites (Krysan et al, 2009). Overall, the two studies suggest that blacks may perceive the least distress in diverse neighborhoods, whereas whites would be the least distressed in all white neighborhoods and the effects of diverse neighborhoods would depend on the beliefs that whites have of minorities.…”
Section: Racial Heterogeneity and Mental Healthmentioning
confidence: 99%
“…Still, the researchers were not entirely forthcoming in this group. They did not typically provide the questions used to assess consensus in the focus group, and in one case (Krysan, et al 2009) it was unclear how many groups were carried out in the pretest.…”
Section: :303)mentioning
confidence: 99%
“…As Table 2 demonstrates, all four articles that most clearly utilize the group unit of analysis do so as pretests. Two articles (Gibson 2004;Sue and Telles 2007) use focus groups to pretest a survey instrument; one article (Ghazal Read and Oselin 2008) uses them to pretest interview questions; and the fourth article (Krysan, et al 2009) undertakes focus groups as a pretest for an experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation